2011
DOI: 10.4049/jimmunol.1004122
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD8+ T Cell Priming in the Absence of NK Cells Leads to Enhanced Memory Responses

Abstract: It is uncertain whether NK cells modulate T cell memory differentiation. By using a genetic model that allows the selective depletion of NK cells, we show in this study that NK cells shape CD8+ T cell fate by killing recently activated CD8+ T cells in an NKG2D- and perforin-dependent manner. In the absence of NK cells, the differentiation of CD8+ T cells is strongly biased toward a central memory T cell phenotype. Although, on a per-cell basis, memory CD8+ T cells generated in the presence or the absence of NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
114
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 17 publications
14
114
3
1
Order By: Relevance
“…Unfortunately, studies of immune responses in NKG2D-deficient mice are complicated by altered NK cell development and function in these animals. NK cells limit effector and memory CD8 T cell expansion in a partially NKG2D-dependent way (18,19). Moreover, NK cells of Klrk1 2/2 mice are hyperresponsive, resulting in enhanced viral clearance on day 4 postinfection (7).…”
Section: Nkg2d Promotes Memory Formation and Antiviral Protectionmentioning
confidence: 99%
“…Unfortunately, studies of immune responses in NKG2D-deficient mice are complicated by altered NK cell development and function in these animals. NK cells limit effector and memory CD8 T cell expansion in a partially NKG2D-dependent way (18,19). Moreover, NK cells of Klrk1 2/2 mice are hyperresponsive, resulting in enhanced viral clearance on day 4 postinfection (7).…”
Section: Nkg2d Promotes Memory Formation and Antiviral Protectionmentioning
confidence: 99%
“…It has been reported that NK cells regulate T cell responses through multiple direct and indirect mechanisms, including NK cell-mediated killing of activated CD8 + T cells (14,15,(18)(19)(20)(21), CD4 + T cells (18,19,22,23), and also of dendritic cells (DCs) (12,24,25). However, little is known about a possible NK cell-mediated inhibitory/regulatory role during antitumor immune responses.…”
mentioning
confidence: 99%
“…Along this line, Soderquest et al (1) reported that NK cells induced apoptosis in recently activated CD8…”
Section: T Cell Priming In the Absence Of Nk Cells Leads To Enhanced mentioning
confidence: 86%